Hemodynamic Effects of Positive Airway Pressure: A Cardiologist’s Overview - Anna Di Cristo; Andrea Segreti; Nardi Tetaj; Simone Pasquale Crispino; Emiliano Guerra; Emanuele Stirpe; Gian Paolo Ussia; Francesco Grigioni (Journal of Cardiovascular Development and Disease)
Positive airway pressure (PAP) therapy is widely used to manage both acute and chronic respiratory failure and plays an increasingly important role in cardiology, particularly in treating patients with respiratory comorbidities. PAP, including continuous positive airway pressure and noninvasive ventilation, significantly impacts hemodynamics by altering intrathoracic pressure, affecting preload, afterload, and stroke volume. These changes are crucial in conditions such as acute cardiogenic pulmonary edema, where PAP can enhance gas exchange, reduce the work of breathing, and improve cardiac output. PAP reduces the left ventricular afterload, which in turn increases stroke volume and myocardial contractility in patients with left-sided heart failure. However, the role of PAP in right ventricular function and its effects on venous return and cardiac output are critical in the cardiac intensive care setting. While PAP provides respiratory benefits, it must be used cautiously in patients with right heart failure or preload-dependent conditions to avoid adverse outcomes. Additionally, in recent years, the use of PAP has expanded in the treatment of severe obstructive sleep apnea and obesity hypoventilation syndrome, both of which significantly influence cardiovascular events and heart failure. This review provides an in-depth analysis of the hemodynamic effects of PAP in cardiovascular disease, focusing on its impact on ventricular function in both acute and chronic conditions. Evaluating clinical studies, guidelines, and recent advancements offers practical insights into the physiological mechanisms and key clinical considerations. Furthermore, this review aims to serve as a helpful guide for clinicians, assisting in decision-making processes where PAP therapy is applied.